MODERN TRENDS IN MECHANICS OF TECTONIC EARTHQUAKES - Panteleev, I.A.; Naimark, O.B. (Perm Federal Research Centre Journal, 2015)
The paper submits a review of models of preparation of a tectonic earthquake, based on approaches from various branches of knowledge: mechanics of a deformable body, statistical physics, mathematical statistics, and nonlinear physics. Special attention is paid to the ideology of constructing models through the prism of predicting earthquakes. Merits and demerits of existing models and current trends of their development are discussed.